Searching for medical devices – Practical guidance. (16th November 2021) - Cooper, Chris; Dawson, Sarah; Lefebvre, Carol
Abstract: Systematic reviews of medical devices have generally adopted the same methodology for the conduct of their reviews as reviews of other clinical interventions, in particular, medicines. It has been suggested that these methods may need to be developed to account for the challenges of reviewing the evidence for medical devices when compared to reviews of medicines. The purpose of this research note is to focus on the methods of searching for medical devices. Our aim is to set out guidance on 'how to search' for medical devices. This includes: Defining what you are searching for; How to design a search strategy; Searching bibliographic databases; Searching beyond bibliographic databases; and Search reporting. The research note is written by three experienced searchers/researchers with experience of critically appraising Medical Technologies Evaluation Programme (MTEP) submissions, undertaking systematic searches and/or reviews of medical devices, or developing guidance for searching for studies for systematic reviews of the effectiveness of interventions, including medical devices. The research note includes a worked example of a search for a fictitious medical device.